Ordaining women : culture and conflict in religious organization. - Chaves, Mark (Cambridge (Mass.) Harvard university press, 1997)
In a revealing examination of the complex relationship among religion, social forces, and organizational structure, Ordaining Women draws examples and data from over 100 Christian denominations to explore the meaning of institutional rules about women's ordination. [publisher's description]
Keywords: Ordination of women -- United States; Religion and sociology; Women clergy; Women in Christianity; 254.4*9 -- Vrouw als priester; United States -- Church history -- 20th century